Association of dietary inflammatory index and systemic inflammatory markers with mortality risk in depressed adults: a mediation analysis of NHANES data - Tang, Ming; Chang, Xindong; Zheng, Haiyan; Zeng, Fanyi; Zhang, Guangdong; He, Mingfei; Fang, Qingqing; Yin, Shiwu (Frontiers in Nutrition, 2024)
Background: Previous research has linked systemic inflammatory markers and the Dietary Inflammatory Index (DII) with depression. However, the relationship between DII and these markers, and their impact on mortality risk among depressed adults, remains underexplored. This study aims to explore the association between DII and systemic inflammatory markers and their mediating effect on mortality risk in adults with depression. Methods: This study analyzed data from 4,981 adults with depression in the National Health and Nutrition Examination Survey (NHANES). This study quantified dietary inflammatory potential with the DII and systemic inflammation with the Systemic Immune-Inflammation Index (SII) and Systemic Inflammation Response Index (SIRI). Cox proportional hazards regression and inverse probability weighting evaluated the impact of DII, SII, and SIRI on mortality risk in depressed adults, as well as their mediating effects. Multiple linear regression analyzed the associations between DII and SII/SIRI. Restricted cubic spline analysis explored the non-linear relationship between DII and mortality risk. Results: In adjusted regression models, DII, SII, and SIRI were significantly associated with all-cause mortality risk in depressed adults, with HRs (95% CIs) from 1.333 to 1.497 (1.051-1.233, 1.689-1.832). DII was linearly related to SII, with βs (95% CIs) from 0.001 to 0.121 (0.001-0.017, 0.001-0.224). SII significantly mediated the DII-mortality risk link, especially in males (8.07%). The DII-mortality relationship was linear (P nonlinear = 0.174), with a beneficial threshold at 1.62. Conclusion: DII and SII are associated with increased all-cause mortality risk in depressed adults. The DII-related mortality risk in depression can be partially mediated by SII, with a more pronounced effect in males.